2012
DOI: 10.1016/j.envsci.2011.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural pesticide management in Thailand: status and population health risk

Abstract: As an agricultural country and one of the world’s major food exporters, Thailand relies heavily on the use of pesticides to protect crops and increase yields. During the past decade, the Kingdom of Thailand has experienced an approximate four-fold increase in pesticide use. This increase presents a challenge for the Royal Thai Government in effectively managing and controlling pesticide use based upon the current policies and legal infrastructure. We have reviewed several key components for managing agricultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
123
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 206 publications
(130 citation statements)
references
References 20 publications
4
123
0
3
Order By: Relevance
“…Sillapapiromsuk et al (2013) revealed that burning of agriculture residues (maize residue and rice straw) emitted high Cl -concentrations, and was related to the use of fertilizers and herbicides in the field. Paraquart dichloride (C 12 H 14 N 2 Cl 2 ) is widely used as a herbicide in maize plantation in Thailand, in addition to glyphosate, 2,4-D, ametryn and atrazine (Panuwet et al, 2012). Tao et al (2013) also reported high concentrations of Cl -in PM 2.5 emitted from BB (wheat straw and rape straw) at Chengdu, China.…”
Section: Concentrations Of Pm 25 -Bound Ionsmentioning
confidence: 99%
“…Sillapapiromsuk et al (2013) revealed that burning of agriculture residues (maize residue and rice straw) emitted high Cl -concentrations, and was related to the use of fertilizers and herbicides in the field. Paraquart dichloride (C 12 H 14 N 2 Cl 2 ) is widely used as a herbicide in maize plantation in Thailand, in addition to glyphosate, 2,4-D, ametryn and atrazine (Panuwet et al, 2012). Tao et al (2013) also reported high concentrations of Cl -in PM 2.5 emitted from BB (wheat straw and rape straw) at Chengdu, China.…”
Section: Concentrations Of Pm 25 -Bound Ionsmentioning
confidence: 99%
“…Retailers can either emphasize or downplay environmental and health effects of pesticides, in addition to the classical properties of quality, price and service. This complex process should be guided by adequate knowledge, but most of the available information is too technical for farmers and unlicensed retailers (Panuwet et al 2012). Therefore, supporting and training farmers and retailers by importers, state or non-state actors is crucial.…”
Section: Buying Practicesmentioning
confidence: 99%
“…Coupled with high-yielding crop varieties and increased land for crop production, significant yield improvements were achieved. However, this was realized at the expense of the natural environment and the health of farmers (UNU 2003;Pimentel 2005;Panuwet et al 2012;Hoi et al 2009Hoi et al , 2013Ahouangninou et al 2012). Since Rachel Carson's Silent Spring attention has been given to the hazards of extensive pesticides use in developed and developing countries (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…En general, estos insecticidas son altamente tóxicos para la salud humana y el medio ambiente. Por ejemplo, los insecticidas que contienen metil paratión, malatión, endosulfán, carbaril, dimetoato y metamidofos son de uso corriente en cultivos de repollo en Tailandia (Panuwet, Siriwong, Prapanontol, Ryan, Fiedler, Robson y Boyd, 2012) y son productos que están prohibidos en varios países, y están clasificados por la Organización Mundial de la Salud como sustancias extremadamente peligrosas (1a) y altamente peligrosas (1b) (oms, 1996). El abuso de este tipo de insecticidas en la producción de brasicá-ceas plantea riesgos asociados con fenómenos de resistencia, como es el caso de poblaciones de P. xylostella recolectadas en cultivos de crucíferas en Brasil, que mostraron una resistencia significativa a los insecticidas abamectina (Vertimec ®), metomil (Lannate ®), lufenurón (Match ®), indoxacarb (Steward®) y diafentiuron (Polo ®) (Santos, Siquiera, da Silva y de Farias, 2011).…”
Section: Introductionunclassified